The Effect of Innovation, Working Capital, Liquidity and Sales Growth on Profitability in Pharmaceutical Companies listed on the Indonesian Stock Exchange - Rani Sintya; Hendri Andi Mesta (Financial Management Studies, 2022)
The goal of this studies is to discover whether there's an effect of innovation, operating capital, liquidity and sales increase on profitability. The item of studies is pharmaceutical businesses indexed at the IDX in the course of the 2016-2020 length. The sample choice in this have a look at used a purposive sampling method and the information used on this take a look at were secondary data obtained from the IDX internet site www.idx.co.id. The data analysis technique used is multiple linear regression analysis and hypothesis testing using SPSS 26. The results of the study state that innovation has no effect on profitability with a significance of 0.664. Working capital has an effect on profitability with a significance of 0.004. Liquidity has an effect on profitability with a significance of 0.002. Sales growth has an effect on profitability with a significance of 0.036.